2017
DOI: 10.1159/000451006
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Sensing Receptor Genetic Polymorphisms and Risk of Developing Nephrolithiasis in a Chinese Population

Abstract: Objective: To evaluate the association between calcium-sensing receptor (CaSR) Arg990Gly (rs1042636, A > G), Ala986Ser (rs1801725, G > T) polymorphisms, and urolithiasis risk. Methods: Polymorphisms mentioned above were genotyped in a hospital-based case-control study of 615 patients diagnosed with nephrolithiasis and 315 kidney stone-free controls in a Chinese population using the SNaPshot method. Results: The results indicated a significantly increased risk associated with CaSR Arg990Gly GG genotypes (OR 1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Vezzoli et al were the first to report a positive association of the non-synonymous CaSR gene variant rs1042636 (p.R990G) in exon 7 with urinary Ca excretion in a cohort of kidney SF [88]. The association of this CASR variant with urinary Ca excretion and calcium nephrolithiasis has been reproduced in other ethnic cohorts [86,89]. Several other non-synonymous (rs1801725 and rs1801726), intronic (rs17251221 and rs1501899) and 5' UTR (rs7652589) CASR gene variants have also been associated with kidney stone disease in recent years (Table 1) [86,[89][90][91][92][93][94].…”
Section: Calcium-sensing Receptormentioning
confidence: 96%
See 1 more Smart Citation
“…Vezzoli et al were the first to report a positive association of the non-synonymous CaSR gene variant rs1042636 (p.R990G) in exon 7 with urinary Ca excretion in a cohort of kidney SF [88]. The association of this CASR variant with urinary Ca excretion and calcium nephrolithiasis has been reproduced in other ethnic cohorts [86,89]. Several other non-synonymous (rs1801725 and rs1801726), intronic (rs17251221 and rs1501899) and 5' UTR (rs7652589) CASR gene variants have also been associated with kidney stone disease in recent years (Table 1) [86,[89][90][91][92][93][94].…”
Section: Calcium-sensing Receptormentioning
confidence: 96%
“…variant (c.11C>T, p.Thr4Met) associated with reduced urinary Ca excretion in North American population[85]. variants (p.A986S, p.R990G and p.Q1011E) in Exon 7 associated with increased risk for kidney stones and increased urinary Ca excretion[88,86,89]. UTR variants associated with increased risk for kidney stones[86,[89][90][91][92][93][94].CASR rs7627468 -Variant in a regulatory region of the first intron identified by GWAS associated with increased risk for kidney stones, increased serum total and ionized Ca and decreased 25-hydroxy vitamin D[7].UMOD rs4293393 -Variant identified by GWAS associated with increased risk for CKD and gout but reduced risk for kidney stones in Icelandic and Dutch population[95].…”
mentioning
confidence: 99%
“…Our searching strategy identified eight papers evaluating the association between CaSR R990G gene polymorphism and the risk of urolithiasis. Of those, four papers [26][27][28][29] showed that R990G gene polymorphism was associated with the risk of urolithiasis with variable odd ratio, ranging from 1.24 to 8.07 (G vs. R). On the other hand, four other studies [30][31][32][33] failed to confirm the correlation.…”
Section: Discussionmentioning
confidence: 99%
“…In non-uremic subjects, CASR rs1801725 SNP was found as attributed to the development of calcium nephrolithiasis [32, 33] and simultaneously higher serum calcium levels [33] or not associated with calcium kidney stone formation [17, 34, 35]. In HD patients, CASR rs1801725 SNP did not associate solely either with nephrolithiasis-related ESRD or serum calcium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The CASR rs1801725 polymorphism was not associated with the risk of nephrolithiasis development in a Chinese population [17]. In HD patients, rs7652589 SNP correlated with nephrolithiasis-related ESRD without interaction with SNPs of vitamin D signaling pathway genes [6].…”
Section: Introductionmentioning
confidence: 99%